Parvovirus (B19V) infection in pregnant women and infants - V. V. Vasiliev; E. A. Murina; S. V. Sidorenko; A. L. Mukomolova; S. K. Kuyoumchan; O. L. Voronina; I. G. Miroshnichenko; V. A. Matsko (Журнал инфектологии)
The modern detailed data about different aspects of parvovirus infection presented in this review. Based on the analysis of literature, the ethiology epidemiology, clinical manifestations of this disease described. The special attention pays to mechanisms of virus’s pathologic impact to fetus. The authors widely take up the possibilities to estimate risks of congenital parvovirus infection, antenatal diagnostics measures, interpretation of the lab and instrumental results. Therapeutic approaches in different clinical situations described, possibilities of prophylaxis discussed.